Telechelic amphiphilic metallopolymers end-functionalized with platinum(ii) complexes: synthesis, luminescence enhancement, and their self-assembly into flowerlike vesicles and giant flowerlike vesicles. Issue 32 (19th July 2019) - Meng, Weisheng; He, Qun; Yu, Manman; Zhou, Yufeng; Wang, Chen; Yu, Bingran; Zhang, Bin; Bu, Weifeng
Abstract : Telechelic amphiphilic metallopolymers can self-assemble in solution to create nanosized flowerlike vesicles, where the two platinum(ii ) complex ends are connected to the same vesicular core and the central PEG chains form loops as a corona. Abstract : Here we have designed and synthesized a series of platinum(ii ) complex end-difunctionalized poly(ethylene glycol)s (PEGs). For the first time, these telechelic amphiphilic metallopolymers can self-assemble in solution to create nanosized flowerlike vesicles, where the two platinum(ii ) complex ends are connected to the same vesicular core and the central PEG chains form loops as a corona. Such a self-assembly process correlates well with spectroscopic changes and luminescence enhancements that originate from Pt⋯Pt and π–π stacking interactions. Moreover, thermal annealing of the nanosized flowers leads to a morphological transformation to micrometer size, giant flowerlike vesicles. The present work, combining telechelic polymers with metal complexes, will open up a new approach for the design of functional metallopolymers with controllable self-assembly.